T-3t+6-2=

Simple and best practice solution for T-3t+6-2= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for T-3t+6-2= equation:


Simplifying
T + -3t + 6 + -2 = 0

Reorder the terms:
6 + -2 + T + -3t = 0

Combine like terms: 6 + -2 = 4
4 + T + -3t = 0

Solving
4 + T + -3t = 0

Solving for variable 'T'.

Move all terms containing T to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + T + -4 + -3t = 0 + -4

Reorder the terms:
4 + -4 + T + -3t = 0 + -4

Combine like terms: 4 + -4 = 0
0 + T + -3t = 0 + -4
T + -3t = 0 + -4

Combine like terms: 0 + -4 = -4
T + -3t = -4

Add '3t' to each side of the equation.
T + -3t + 3t = -4 + 3t

Combine like terms: -3t + 3t = 0
T + 0 = -4 + 3t
T = -4 + 3t

Simplifying
T = -4 + 3t

See similar equations:

| 12+w=16 | | 1234567890-9856219= | | 2(c-7)+3(x-1)=4x+3 | | 16(x+3)=4(4x+1)+44 | | X+7+23x=23 | | -2x-4(-5x+18)=144 | | 1-(11x+3)=5 | | T(15-5t)=0 | | 0.5(x-3)=7 | | -8(t-2)-3(3t+1)=-4 | | 40*3= | | -25=4x+5 | | 19=-11+2x | | 2n+14-4n=26 | | 56x^2=79x-9 | | 3y+5=2x+1 | | 5x-3=3+2x | | 13-9x=-50 | | y+3=-11 | | 12=7x+25 | | 12x+124=-32 | | 79=7x+12 | | 120-11x=-34 | | x+4-5x=3 | | 0.20s+0.32=520s | | (8y-7x)(8y+7x)= | | 0.18M+16=40.54M | | 12-7x=-6 | | -9-5x=-54 | | 10-3t=4 | | 0.2b+9=0.5b+18 | | 3x*6=39 |

Equations solver categories